USE OF MULTICRITERIAL OPTIMIZATION IN FURNITURE MANUFACTURING PROCESS - Kłosowski, Grzegorz; Kozłowski, Edward (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
This paper concerns the use of integer linear programming in a multi-criteria optimization. The aim of the research was to develop a model of the decision support system allowing simultaneous minimization of the intermediate products stocks level and waste generated in the process of cutting. The goal of controller was to select the appropriate cutting program, including production orders, the current inventory and limits on permissible stocks levels.